Circadian variation of stroke: a hospital based study - Fodor, Dana Marieta; Babiciu, Ioana; Perju-Dumbrava, Lacramioara (Medicine and Pharmacy Reports, 2014)
Aims and Background The circadian pattern of stroke occurrence variation has been recognized with certain differences between authors and stroke types. The underlying reason may be related to exogenous factors (cyclic physical activity, including sleep–awake cycles and assuming the up-right posture) and endogenous factors, with their diurnal variation (blood pressure, hemostatic balance, autonomic system activity). The aims of the present study are to investigate the existence of a circadian variation of stroke and the possible differences between stroke subtypes in the Cluj Napoca area. Materials and Method The stroke event data were acquired from the Patient Records of a consecutive series of 1083 patients admitted through the Emergency Room at Neurology Departments I and II of the District Hospital of Cluj Napoca, between 1 January 2012 and 31 December 2012. The classifiable onset time was assigned to one of four six-hour intervals: 00.01-06.00 (night), 06.01-12.00 (morning), 12.01-18.00 (afternoon) and 18.01-24.00 (evening). Demographic data and vascular risk factors were recorded. Results All three stroke types (ischemic stroke, hemorrhagic stroke and subarachnoid hemorrhage) have shown a circadian variation regarding their occurrence, with the peak of incidence in the morning and the nadir during nighttime. This circadian pattern is independent by demographic factors and vascular risk factors. Conclusion Our study confirmed the circadian variation of onset occurrence for all stroke subtypes. Some triggering factors promote ischemic stroke and prevent hemorrhagic stroke. The diurnal pattern of variation with the higher incidence in the morning and the lower in the night may lead to chrono-therapeutic and preventive approach (chrono-therapy of the risk factors), which targets the period of the highest vulnerability after awaking.